Nurse- and peer-led self-management programme for patients with an implantable cardioverter defibrillator; a feasibility study - van Eijk Jacques; van Hoef Elisabeth FM; Dijkman-Domanska Barbara K; van Haastregt Jolanda CM; Smeulders Esther STF; Kempen Gertrudis IJM (BMC, 2007)
Abstract Background The prevalence of cardiovascular disease is increasing. Improved treatment options increase survival after an acute myocardial infarction or sudden cardiac arrest, although patients often have difficulty adjusting and regaining control in daily life. In particular, patients who received an implantable cardioverter defibrillator (ICD) experience physical and psychological problems. Interventions to enhance perceived control and acceptance of the device are therefore necessary. This paper describes a small-scale study to explore the feasibility and the possible benefits of a structured nurse- and peer-led self-management programme ('Chronic Disease Self-Management Program' - CDSMP) among ICD patients. Methods Ten male ICD patients (mean age = 65.5 years) participated in a group programme, consisting of six sessions, led by a team consisting of a nurse specialist and a patient with cardiovascular disease. Programme feasibility was evaluated among patients and leaders by measuring performance of the intervention according to protocol, attendance and adherence of the participating ICD patients, and patients' and leaders' opinions about the programme. In addition, before and directly after attending the intervention, programme benefits (e.g. perceived control, symptoms of anxiety and depression, and quality of life) were assessed. Results The programme was conducted largely according to protocol. Eight patients attended at least four sessions, and adherence ranged from good to very good. On average, the patients reported to have benefited very much from the programme, which they gave an overall report mark of 8.4. The leaders considered the programme feasible as well. Furthermore, improvements were identified for general self-efficacy expectancies, symptoms of anxiety, physical functioning, social functioning, role limitations due to physical problems, and pain. Conclusion This study suggests that a self-management programme led by a team consisting of a nurse specialist and a patient with cardiovascular disease seems feasible according to both patients and leaders. The programme may improve general self-efficacy expectancies, symptoms of anxiety, and quality of life (physical functioning, social functioning, role limitations due to physical problems, and pain) as well. Further investigation of the programme's effectiveness among a larger sample of ICD patients or other patient groups with cardiovascular disease, is recommended.